Monitoring changes in the P53 gene mutation to diagnose oral cancer - Thangavel Lakshmipriya; Subash C.B. Gopinath (Oral Oncology Reports)
Oral squamous cell carcinoma (OSCC) is a common type of tumor that develops in the mucosal epithelium of the oral cavity. Approximately 377,713 OSCC cases were reported worldwide, and the incidence of OSCC is expected to increase by approximately 40 % by 2040. Various factors, such as the use of tobacco, betel quid, alcohol, and human papillomavirus infection, are the most common causes of OSCC. Recently, researchers found that some DNA gene mutations are responsible for OSCC. It was discovered that changes in DNA in the oropharynx and oral cavity can become cancerous and lead to oral cancer. In particular, the p53 gene mutation plays a significant role in the development of OSCC. When p53 DNA is damaged by chemical or physical factors, an increase in p53 gene transcription is noted, and the p53 protein becomes concentrated, which arrests the cell cycle at the G1/S phase, leading to cancerous characteristics in the cell. Recently, researchers identified that the detection of p53 gene mutations may help in the early identification of oropharyngeal and oral tumors and also assist in determining the response to radiation therapy and surgery for OSCC.